Immunological risk factors for sepsis-associated delirium and mortality in ICU patients - Lei, Wen; Ren, Zhiyao; Su, Jun; Zheng, Xinglong; Gao, Lijuan; Xu, Yudai; Deng, Jieping; Xiao, Chanchan; Sheng, Shuai; Cheng, Yu; Ma, Tianshun; Liu, Yu; et al. (Frontiers in Immunology, 2022)
Background: A major challenge in intervention of critical patients, especially sepsis-associated delirium (SAD) intervention, is the lack of predictive risk factors. As sepsis and SAD heavily entangle with inflammatory and immunological process, thus, to identify the risk factors of SAD and mortality in intensive care unit (ICU) and determine the underlying molecular mechanisms, the peripheral immune profiles of patients in ICU were characterized. Methods: This study contains a cohort of 52 critical patients who were admitted to the ICU of the First Affiliated Hospital of Jinan University. Comorbidity including sepsis and SAD of this cohort was diagnosed and recorded. Further, peripheral blood samples were collected on day 1, 3 and 5 of admission for peripheral immune profiling with blood routine examination, flow cytometry, ELISA, RNA-seq and qPCR. Results: The patients with SAD had higher mortality during ICU admission and within 28 days of discharge. Compared with survivors, non-survivors had higher neutrophilic granulocyte percentage, higher CRP concentration, lower monocyte count, lower monocyte percentage, lower C3 complement level, higher CD14loCD16+ monocytes percentage, and higher levels of IL-6 and TNFα. The CD14hiCD16- monocytes percentage manifested favorable prediction values for the occurrence SAD. Differentially expressed genes between non-survival and survival group were mainly associated with immune response and metabolism process. The longitudinal expression pattern of SLC2A1 and STIMATE were different between non-survivors and survivors, which were validated by qPCR. Conclusions: Non-survival critical patients have distinct immune profile when compared with survival patients. CD14hiCD16- monocytes prevelance and expression level of SLC2A1 and STIMATE may be predictors of SAD and 28-day mortality in ICU patients.